2016
DOI: 10.1136/bmjopen-2016-013995
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Senior Dance on risk factors for falls in older adults (DanSE): a study protocol for a randomised controlled trial

Abstract: IntroductionStrong evidence shows that exercise is effective to improve fall risk factors among older people. However, older people's participation and adherence to exercise programmes is suboptimal. Type of exercise and apathy are reported to be barriers to exercise participation, suggesting that new effective interventions are needed. The primary aim of this randomised controlled trial is to investigate the effect of Senior Dance plus brief education for falls prevention on balance among people aged 60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
2
17
0
4
Order By: Relevance
“…The beneficial effects this training has on both the balance score and the fear of falling are in line with findings of many empirical studies on physical activity (e.g., Buchner et al, 1997;Chang et al, 2004;Franco et al, 2016;Gillespie et al, 2012;Sousa et al, 2017) and combined programs (El-Khoury et al, 2013;2015;Gillespie et al, 2012;Shumway-cook et al, 2007). These results confirm that elderly people who have had a previous fall/falls may benefitin terms of balance and fear of fallingfrom training programs based on therapeutic patient education and/or on physical activities.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The beneficial effects this training has on both the balance score and the fear of falling are in line with findings of many empirical studies on physical activity (e.g., Buchner et al, 1997;Chang et al, 2004;Franco et al, 2016;Gillespie et al, 2012;Sousa et al, 2017) and combined programs (El-Khoury et al, 2013;2015;Gillespie et al, 2012;Shumway-cook et al, 2007). These results confirm that elderly people who have had a previous fall/falls may benefitin terms of balance and fear of fallingfrom training programs based on therapeutic patient education and/or on physical activities.…”
Section: Discussionsupporting
confidence: 87%
“…Many preventive intervention programs based on reported risk factors have been established and evaluated (for a review, Gillespie et al, 2012). A substantial number of studies have shown that physical exercise interventions have proved to be effective in reducing the fall risk, including Tai Chi (e.g., Wong, Lin, Chou, Tang, & Wong, 2001), aerobic and resistance exercise (Sousa, Mendes, Silva & Oliveira, 2017), dancing (Franco et al, 2016), endurance, muscle strengthening, stretching, and balance training (e.g., Buchner et al, 1997;Gardner, Robertson, & Campbell, 2000), or combinations of these activities (Shumway-Cook, Grubner, Baldwin, & Liao, 1997;Skelton & Dinan, 1999). These studies have shown an improvement in lower limb strength, balance, and functional abilities in addition to reduced fall risk as well as fear of falling (Howe, Rochester, Jackson, Banks, & Blair, 2007;Sherrington et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Balance is a strong risk factor for falls and has been used as a proxy measure of the possible impact of an intervention on falls in circumstances where resources do not allow for the conduct of an adequately powered trial (which would require approximately 500 participants), with falls as the primary outcome. Functional measures of balance are valid predictors of falls 18 19. We will also extract measures of fall rate, fall risk, fear of falling where they are included in studies as secondary outcomes.…”
Section: Methods and Analysismentioning
confidence: 99%
“…To ensure allocation concealment, randomization to groups will be undertaken by an independent researcher who will be instructed not to inform the participants or other researchers. 34 …”
Section: Methodsmentioning
confidence: 99%